Parallel Currency Markets in Developing Countries : Theory, Evidence, and Policy Implications. (IMF Working Papers; Working Paper, 1990)
The paper reviews recent theoretical and empirical developments in the analysis of informal currency markets in developing countries. The basic characteristics of these markets are highlighted, and alternative analytical models to explain them are discussed. The implications for exchange rate policy -including imposition of foreign exchange restrictions, devaluation, and unification of exchange markets- in countries with a sizable parallel market are also examined.